Cognitive-Behavioral Therapy for Treating Videogame Dependence in School-aged Children - Moses Onyemaechi Ede; Chinedu Ifedi Okeke (Bulletin of Counseling and Psychotherapy, 2023)
This study examined the effectiveness of cognitive-behaviour therapy on schoolchildren with videogame dependency in a sample of Nigerian schoolchildren. This study was conducted in Enugu metropolis Enugu State Nigeria. A randomized-controlled pretest and posttest design was adopted. Out of 86 schoolchildren that participated in the study, 43 children were exposed to the intervention while 43 did not receive treatment as usual (TAU). The treatment lasted for eight weeks with one session per week. During the study, the participants were assessed at three time points using videogame addiction scale for children. The data collected were statistically analyzed using the multivariate statistical tool. The multivariate statistical result showed that cognitive-behaviour therapy in reducing videogame dependency among schoolchildren. The practice implications, limitations, and conclusions were also drawn in line with the outcome of this study. This study is one among the few studies in Nigeria that have investigated videogame dependency. Another strength is that study tested the participants at three time points to ascertain the impacts of the intervention.